1999
DOI: 10.1084/jem.189.5.779
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Is Mandatory for CD8+ T Cell–mediated Contact Hypersensitivity

Abstract: Contact hypersensitivity (CHS) is a T cell–mediated skin inflammation induced by epicutaneous exposure to haptens in sensitized individuals. We have previously reported that CHS to dinitrofluorobenzene in mice is mediated by major histocompatibility complex (MHC) class I–restricted CD8+ T cells. In this study, we show that CD8+ T cells mediate the skin inflammation through their cytotoxic activity. The contribution of specific cytotoxic T lymphocytes (CTLs) to the CHS reaction was examined both in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
197
1
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(223 citation statements)
references
References 38 publications
18
197
1
7
Order By: Relevance
“…Mice lacking perforin and/or Fas/Fas ligand pathways necessary for T cell-mediated cytotoxity were compared with wild-type animals. It was found that although mice lacking both pathways were able to generate hapten-specific CD8 π T lymphocytes, they were unable to mount CHS reactions (34). Similar conclusions regarding the importance of Fas-induced cell death in the pathogenesis of allergic contact dermatitis and other cutaneous inflammatory reactions derived from studies of human skin (35).…”
Section: Effector Cell Cytotoxic Functionmentioning
confidence: 71%
See 1 more Smart Citation
“…Mice lacking perforin and/or Fas/Fas ligand pathways necessary for T cell-mediated cytotoxity were compared with wild-type animals. It was found that although mice lacking both pathways were able to generate hapten-specific CD8 π T lymphocytes, they were unable to mount CHS reactions (34). Similar conclusions regarding the importance of Fas-induced cell death in the pathogenesis of allergic contact dermatitis and other cutaneous inflammatory reactions derived from studies of human skin (35).…”
Section: Effector Cell Cytotoxic Functionmentioning
confidence: 71%
“…The question is to what extent cytotoxic mechanisms are required for CHS reactions effected by CD8 π cells, or other cellular effectors. The need for cytotoxic activity was investigated in a mouse model of CHS to DNFB in which the predominant or exclusive effectors were found to be CD8 π cells (34). Mice lacking perforin and/or Fas/Fas ligand pathways necessary for T cell-mediated cytotoxity were compared with wild-type animals.…”
Section: Effector Cell Cytotoxic Functionmentioning
confidence: 99%
“…In C and D are CD4 ϩ and CD8 ϩ T cell lines, respectively, prepared from the skin of a third patient. direct cytotoxicity (7,13,22). ACD is generally considered as a model of Th1 cell-mediated disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Upon skin painting, the hapten is taken up by skin DC which migrate to proximal lymph nodes and activate specific T cells. Since the hapten can stay in the skin for a few days in its antigenic form, effector CD8 + T cells are recruited and activated in the dermis and induce CHS through a process involving cytotoxicity and IFNγ synthesis [38,39]. We used suboptimal concentrations of DNFB so that the CHS reaction observed at day 5 was only moderate in intensity and magnitude (Fig.…”
Section: Lpc Primes Specific T Cell Responses In Vivomentioning
confidence: 99%